Carbachol-induced network oscillations in an in vitro limbic system brain slice. (21st April 2017) - Lévesque, Maxime; Cataldi, Mauro; Chen, Li-Yuan; Hamidi, Shabnam; Avoli, Massimo
Highlights: Activation of muscarinic receptors induces theta oscillations (5–12 Hz) in vitro. Theta activity often initiates in CA3/subiculum and propagates to entorhinal cortex. GABAA receptor activity modifies the pattern of carbachol-induced theta activity. Changes in the theta generating system could contribute to seizures. Abstract: We employed simultaneous field potential recordings from CA3, subiculum and entorhinal cortex in an in vitro brain slice preparation to understand the involvement of these limbic areas in the generation of the field potential oscillations that are induced by bath application of the muscarinic receptor agonist carbachol. Regularly spaced oscillations that mainly presented at theta frequency range (5–12 Hz) occurred synchronously in all three structures in the presence of carbachol. These oscillations, which disappeared when slices were perfused with pirenzepine or with glutamatergic receptor antagonists, were categorized as short (<4 s) and long (>4 s) with short events oscillating at higher frequencies than long events. Field oscillations were highly synchronized between regions and latency analysis revealed that they often initiated in the entorhinal cortex later than in the other two structures. Blocking GABAA receptors modified the activity patterns of both short and long oscillations and decreased their coherence in the theta frequency range. Finally, blocking KCC2 activity disclosed a pattern of recurrent short oscillations. Our results suggest that in the presence of carbachol both subiculum and CA3 most often drive theta generators in the entorhinal cortex and that these oscillations are influenced but not abolished by altering GABAA receptor signaling.